Regional Needs Assessment for Mainstreaming Climate Smart Agriculture and Climate Information Services into Universities’ Curricula in West Africa - Amponsah, William; Sawaneh, Mamma; Idrissou, Mouhamed; Hounkpe, Jean; Oluleye, Ayodeji; Kone, Daouda; Segnon, Alcade Christel; Zougmore, Robert Bellarmin (2025)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Project builds on the initiatives and achievements under the CGIAR Research Programme on the Climate Change, Agriculture and Food Security (CCAFS) in Africa. With a focus on climate-smart agriculture (CSA) technologies and on climate information services (CIS), the AICCRA project includes an important capacity development component for the benefit of countries in Africa. This study conducted a regional needs assessment in capacity building for the development of curricula or training programmes in CIS and CSA in tertiary institutions in five (5) West African countries (Benin, Ghana, Niger, The Gambia and Togo). Using an online data collection tool (kobo collect), the study targets university lecturers and researchers in these countries by sending research questionnaires and making regular follow ups for a period of 3 to 4 months. A total of 54 responses were collated, analysed and put into perspectives. Descriptive statistics represented by percentages and frequencies were used to analyse the quantitative data whereas content and thematic analyses were used to analyse the qualitative data. The results showed that the background and expertise of the respondents were in Agriculture, Environment and Climate-related Sciences, which are very relevant for capacity building in Climate Information Services (CIS) and Climate Smart Agriculture (CSA). The findings also showed that the majority of the respondents’ demonstrated knowledge of the concepts of CSA and could adequately explain these concepts. Moreover, those with no prior knowledge showed willingness to learn about the concepts. Most of the respondents expressed having access to climate and weather information, predominantly rainfall and temperature from the national television in the study countries as the main source. The study concludes that there is a need to strengthen capacities of institutions in the regions about these two concepts through short course training using in person deliveries and online platforms but with better coordination by developing comprehensive training programs that will be more interactive and focused oriented.